2017
DOI: 10.1016/j.molcel.2016.11.007
|View full text |Cite|
|
Sign up to set email alerts
|

Gene Architectures that Minimize Cost of Gene Expression

Abstract: SUMMARY Gene expression burdens cells by consuming resources and energy. While numerous studies have investigated regulation of expression level, little is known about gene design elements that govern expression costs. Here, we ask how cells minimize production costs while maintaining a given protein expression level and whether there are gene architectures that optimize this process. We measured fitness of ~14,000 E. coli strains, each expressing a reporter gene with a unique 5′ architecture. By comparing cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
89
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 49 publications
(70 reference statements)
3
89
3
Order By: Relevance
“…Our in vitro and in vivo assays as well as our experimental data with different proteins and vectors (Fig 3 and Supplementary Fig 9-15) indicate striking differences in translation efficiency that is driven by nucleotide sequence at the 7-15 positions and that of the amino acid at the 3-5 positions of the openreading frame. The position of the randomized sequence in our results (Fig 1-3, Supplementary Fig 2-15) as well as the previous studies 7,8,11,12,14,16,21,25 indicated that translation initiation or early elongation steps could be influencing efficacy of protein expression. To address this possibility, we assayed the efficiency of initiation complex formation and kinetics of peptidyl transfer using a well-defined in vitro E.…”
Section: Mainsupporting
confidence: 87%
See 1 more Smart Citation
“…Our in vitro and in vivo assays as well as our experimental data with different proteins and vectors (Fig 3 and Supplementary Fig 9-15) indicate striking differences in translation efficiency that is driven by nucleotide sequence at the 7-15 positions and that of the amino acid at the 3-5 positions of the openreading frame. The position of the randomized sequence in our results (Fig 1-3, Supplementary Fig 2-15) as well as the previous studies 7,8,11,12,14,16,21,25 indicated that translation initiation or early elongation steps could be influencing efficacy of protein expression. To address this possibility, we assayed the efficiency of initiation complex formation and kinetics of peptidyl transfer using a well-defined in vitro E.…”
Section: Mainsupporting
confidence: 87%
“…Interestingly, this difference is higher than previously reported for expression of 14,000 variants of super-folder green fluorescent protein (sfGFP) with randomized promoters, ribosome binding sites, and first 11 codons 11 , or when 94 % of the eGFP protein was recoded using synonymous codons 12 . These results indicated that the overall expression of the protein could be significantly changed as a result of differences in the N-terminal sequence that encompasses the first 5 amino acids of the protein, in other words nucleotides [7][8][9][10][11][12][13][14][15] of the open-reading frame (ORF) corresponding to the first ribosome footprint after initiation ( Supplementary Fig 1).…”
Section: Mainmentioning
confidence: 99%
“…R 2 = 15 0.11) and largely driven by less stable, highly deleterious mutations. We could not detect a relationship between change in mRNA stability and fitness for synonymous mutations, even when we account for the possibility of strong 5' end secondary structures by adding a position term reflecting distance from the start codon (17).…”
mentioning
confidence: 81%
“…However, despite the proximity of this question to the heart of the Central Dogma, significant uncertainty remains concerning the answers. Two recently published papers (Kelsic et al 2016, Frumkin et al 2017) illustrate the power of high-throughput systems biology methods to provide insight into complex biological questions of this kind, while they simultaneously raise new questions highlighting the complexity of the biological and evolutionary phenomena related to codon usage.…”
mentioning
confidence: 99%
“…The recently published papers by Kelsic et al (2016) and Frumkin et al (2017) both illustrate the impressive power of systems biology approaches to rapidly characterize biological systems in greater depth and breadth than possible using traditional genetic and biochemical experimentation. However, the conceptual, mechanistic, and evolutionary complexities influencing codon usage are likely to keep both systems biologists and traditional molecular biologists busy for a considerable period of time before a confident understanding is achieved of the related principles and phenomena.…”
mentioning
confidence: 99%